2012
DOI: 10.1136/eb-2012-100872
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid reduces blood transfusion in surgical patients while its effects on thromboembolic events and mortality are uncertain

Abstract: Commentary on: Ker K, Edwards P, Perel P, et al. Effect of tranexamic acid on surgical bleeding: systematic review and cumulative meta-analysis. BMJ 2012;344:e3054.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 5 publications
1
28
0
Order By: Relevance
“…In addition, concerns still exist about the safety of TXA in primary unilateral THA. 15,32 The present study therefore substantially extends our own previous work and the literature more broadly by comparing, in a large sample, the efficacy of TXA administered topically, intravenously or both.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In addition, concerns still exist about the safety of TXA in primary unilateral THA. 15,32 The present study therefore substantially extends our own previous work and the literature more broadly by comparing, in a large sample, the efficacy of TXA administered topically, intravenously or both.…”
Section: Discussionsupporting
confidence: 68%
“…While routes of TXA administration have been compared for total knee arthroplasty by our own group, few studies have directly compared the three routes in THA. In addition, concerns still exist about the safety of TXA in primary unilateral THA …”
Section: Discussionmentioning
confidence: 99%
“…It has been used successfully in orthopedic surgery via an intravenous route, with several studies showing significant reductions in bleeding and risk of transfusion after TKA and THA 12-20 . However, concerns remain over the risk of thromboembolic complications after systemic administration 5, 6 . Topical application leads to 70% lower systemic absorption, and may therefore be a safer alternative to giving it systemically 8 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been isolated case reports of thrombus formation, which has generated concerns over the risk of thromboembolic complications in a patient population already at high risk for deep vein thrombosis and pulmonary embolism. This has prevented the widespread acceptance of the use of IV antifibrinolytics in total joint replacement surgery 5, 6 . Topical application of antifibrinolytics may produce the same efficacy, but with much lower systemic absorption and thus much lower risk for thromboembolic complications.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical trials have identified that intravenous (IV) TXA is effective in reducing perioperative blood loss and the need for subsequent blood transfusions in TKA [15–17]. However, deep venous thrombosis (DVT) after the systemic administration of TXA is still a serious and fatal complication [18]. Therefore, many researchers have focused on the topical application of TXA via drain tube or intra-articular administration, and the topical application of TXA is considered an alternative effective route that entails less risk than IV after TKA [19, 20].…”
Section: Introductionmentioning
confidence: 99%